2020
DOI: 10.3390/antibiotics9110809
|View full text |Cite
|
Sign up to set email alerts
|

Species Distribution, Antimicrobial Resistance, and Enterotoxigenicity of Non-aureus Staphylococci in Retail Chicken Meat

Abstract: Non-aureus staphylococci (NAS), including coagulase-negative staphylococci, have emerged as important causes of opportunistic infections in humans and animals and a potential cause of staphylococcal food poisoning. In this study, we investigated (i) the staphylococcal species profiles of NAS in in retail chicken meat, (ii) the phenotypic and genotypic factors associated with antimicrobial resistance in the NAS isolates, and (iii) the prevalence of classical and newer staphylococcal enterotoxin (SE) genes. A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 59 publications
2
15
0
1
Order By: Relevance
“…No SCC mec type was identified in the case of the four mec A-positive CoNS. These findings are consistent with the results of previous studies in which non-typeable ccr genes were shown to be associated with the heterogeneity of SCC mec elements in methicillin-resistant CoNS strains [ 31 , 33 ].…”
Section: Discussionsupporting
confidence: 93%
“…No SCC mec type was identified in the case of the four mec A-positive CoNS. These findings are consistent with the results of previous studies in which non-typeable ccr genes were shown to be associated with the heterogeneity of SCC mec elements in methicillin-resistant CoNS strains [ 31 , 33 ].…”
Section: Discussionsupporting
confidence: 93%
“…In addition to resistance to β-lactamates, resistance to tetracycline (86%) and erythromycin (78%) was also detected to a greater extent in the isolates we examined. Resistance to erythromycin and tetracycline in S. chromogenes was also detected by Lüthje et al and Lee et al [73,74]. However, in a study by Devries et al, out of 73 staphylococcal strains from different dairy farms, 70 strains of S. chromogemes sensitive to neomycin, gentamicin, erythromycin, enrofloxacin, and penicillin were detected [75].…”
Section: Discussionmentioning
confidence: 84%
“…Resistance to penicillin, ciprofloxacin, and tetracycline of analysed Staphylococcus succinus subsp. casei strains was similar to those observed in other CNS species (Lee et al ., 2020). They showed susceptibility to oxacillin and many other tested antibiotics, which is consistent with the characteristics of methicillin‐sensitive (MS) staphylococcal strains (Kwapisz et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%